PELATIHAN PEMANFAATAN INDIKATOR ALAMI DALAM PRAKTIKUM TITRASI ASAM-BASA SEBAGAI USAHA SUSTAINABILITY PRAKTIKUM KIMIA SMA (Universitas Bengkulu, 2024)
Community service program was aimed at the chemistry teacher that are the member of “Musyawarah Guru Mata Pelajaran (MGMP)” or the community of chemistry teacher in high school in Bengkulu City. The topic of the community service is introducing green chemistry-based practicum module that was developed by a student in Chemistry Education Study Program, using natural indicator that is readily available and easily obtained unlike synthetic indicator that is expensive and difficult to obtain. This e-module encouraged schools to conduct chemistry practicums using surrounding ingredients based on green chemistry concept. The concept of using surrounding materials for practicums excited chemistry teachers as this usually become the biggest obstacle in conducting chemistry practicum in high schools.